Sebaran Ruang Terbuka Hijau dan Peluang Perbaikan Iklim Mikro di Semarang Barat - Dewi Liesnoor Setyowati; Sri Mantini Rahayu Sedyawati (Biosaintifika: Journal of Biology & Biology Education, 2010)
The purpose of the research was detecting green open space (GOS) spread and micro climate  condition  at Semarang Barat,   with  vegetation  spread  and  street  lane  area as  the  object  of  the  research. Population  characteristic  consisted  of  vegetation  area spread, mainly on the shaded  trees composition and micro climate condition by using  purposive sampling technique. The research used descriptive ecologycal approach. The result described that Semarang Barat vegetation spread is included as sparse vegetation, predominantly  by  squat  vegetation  composition with  infrequent  tree  density. Micro climate conditon is categorized as contented climate, but on edge at the daylight.  The condition  is  infl uenced  by  least  along  the  street;  consequently  the micro  climate  of temperature is high with low humidity.  Semarang Barat GOS is 17,1%, so the spacious should be 10,0% enhanced to gain 27,1% GOS to create a better climate. It is suggested to increase squat vegetation composition and quantity along Semarang Barat streets, so vegetation diversity will recovered.Keywords: green open space, micro climate, Semarang Barat